Development of pure and adulterated honey measurement system using multiple frequencies six-port reflectometer (SPR) - Siti Aishah Baharuddin (School of Mechatronic Engineering, Universiti Malaysia Perlis, 2017)
The research objectives are to design and develop a Five-Port ring junction circuit in multiple frequencies use; to develop a microwave measurement system to characterize pure and adulterated honey; to characterize pure and adulterated honey in terms of water content and sucrose content through dielectric properties and complex reflection coefficient.